EFFECT OF GERMINATION ON THE CHEMICAL COMPOSITION AND NUTRITIVE VALUE OF MAIZE GRAIN - BINDIYA SHARMA; ARTI SHARMA; BHAT; ANAND KISHORE (The Bioscan, 2015)
An investigation was conducted to study the effect of germination on nutrients and vitamin content of yellow maize. Results indicated that germination significantly (p ≤ 0.05) increased the protein and ash content from 10.34% and 2.02 % in raw maize to 11.78% and 2.10 % in the germinated maize flour samples. The niacin content also increased from 1.85 to 3.2 mg/kg. However fat was found to decrease from 4.02 % to 3.13 % after germination. Carbohydrates and fiber content were also decreased from 80.67% and 2.12 % to 79.58 % and 1.91 % in germinated maize flour. Energy content decreased from 400.22±12.33and 393.61±9.94 after germi- nation. The present investigation revealed that the germination significantly enhanced the protein, ash and niacin content of maize which is found in limited amounts and in biologically unavailable form in most maize varieties.